A Long Run Structural Macroeconometric Model for Germany - Pu Chen; Elena Schneider; Joachim Frohn (Kiel Institute for the World Economy (IfW), 2007)
The objective of this paper is to apply the method developed in Garratt, Lee, Pesaran, and Shin (2000) to build a structural model for Germany with a transparent and theoretically coherent foundation. The modelling strategy consists of a set of long-run structural relationships suggested by economic theory and an otherwise unrestricted VAR model. It turns out that we can rebuild the structure of the model in Garratt, Lee, Pesaran, and Shin (2003b) for German data. Five long run relations : PPP, UIP, production function, trade balance, and real money balance characterize the equilibrium state of Germany as an open economy in our structural model.
Keywords: C32; E24; 330; Long-Run Structural VAR; Macroeconomic Modelling; A structural Model for Germany; Oil Price Shock